Nanostructured lipid carrier (NLC) in topical preparations: a narrative review of components, manufacturing methods, characteristics and activities - Rizikiyan, Yayan; Sugihartini, Nining; Rais, Ichwan Ridwan (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Nanostructured Lipid Carries NLCs have gained attention in formulation science and nanotechnology due to their biocompatible material and ability to enhance skin penetration. The goal is to create products that can effectively deliver active compounds to desired skin layers with minimal side effects. This review focuses on the use of functionalized NLCs in dermocosmetics, specifically looking at their composition, manufacturing method, characteristics, and role in delivering active compounds. The review obtained articles from databases such as Scopus, Pubmed, and Google Scholar, covering the years 2014-2024. Data search was conducted in May 2024. The search used keywords such as "NLC OR formulation OR dermal OR activity”. By considering factors such as NLC composition, manufacturing method, and impact on compound delivery, researchers aim to optimize NLCs for use in topical preparations. This research contributes to the development of dermocosmetics that can address various skin problems more effectively. The search results from 32 articles gave an overview of the widely used NLC components: solid lipids: glycerol monostearate, compitrol 888 ATO, and tristearin; liquid lipids: myglyol, transcutol, and oleic acid; surfactants: poysorbat 80 and polysorbate 20. The widely used methods were ultrasonication and high pressure homogenization. Frequently performed characterizations include particle size, polydispersity index (PDI), zeta potential, and Entrapment Efficiency (EE). The pharmacological activity of active components loaded into NLCs increased than without NLCs. The active ingredient formulated in NLC can produce better activity compared to the active substance formulated directly in the conventional preparation. The application of nanostructured lipid carrier (NLC) nanoparticles on the skin is very beneficial. These nano systems have shown promising results and more commercial formulations, so it is expected to be done in further research.